2015
DOI: 10.1016/j.copsyc.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Ecological momentary assessment (EMA) of depression-related phenomena

Abstract: Ecological momentary assessment (EMA) is one research method increasingly employed to better understand the processes that underpin depression and related phenomena. In particular, EMA is well suited to the study of affect (e.g., positive and negative affect), affective responses to stress (e.g., emotion reactivity), and behaviors (e.g., activity level, sleep) that are associated with depression. Additionally, EMA can provide insights into self-harm behavior (i.e. suicide and non-suicidal self-injury), and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 50 publications
2
48
0
1
Order By: Relevance
“…The results of this study support similar findings in the recent literature that have shown the significance of remote, in-the-moment (and real-world) approaches to the evaluation of mood state [12,13,17,48]. The feasibility of this approach is supported by the growing usage of mobile devices by patients with mood disorders [9,10,49] and studies that have shown good compliance with mobile monitoring strategies [47,49,79].…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study support similar findings in the recent literature that have shown the significance of remote, in-the-moment (and real-world) approaches to the evaluation of mood state [12,13,17,48]. The feasibility of this approach is supported by the growing usage of mobile devices by patients with mood disorders [9,10,49] and studies that have shown good compliance with mobile monitoring strategies [47,49,79].…”
Section: Discussionsupporting
confidence: 91%
“…Second, these designs capture stress and ruminative processes in a natural setting, versus in structured laboratory paradigms, which may not generalize to real-world experiences. Third, the use of EMA results in many data points, allowing for examination of temporal relationships as well as providing increased confidence in the reliability of the data (Armey, Schatten, Haradhvala, & Miller, 2015; Shiffman, Stone, & Hufford, 2008; Stone et al, 1998; Wenze & Miller, 2010). Furthermore, it has been demonstrated that rumination levels fluctuate over time and are modestly stable at best, suggesting that trait measures may not accurately capture the phenomenology of this construct (Moberly & Watkins, 2008a; Takano & Tanno, 2011).…”
mentioning
confidence: 99%
“…В связи с этим у деструктивности эмпирически обнаруживается множество форм и разнообразный состав. В зарубежных исследованиях, например, фигурирует деструктивная сторона психической травмы (посттравматического стресса) (Ehlers et al, 1998(Ehlers et al, , 2000Feeny et al, 2000), депрессии (Armey et al, 2015;Gilbert, Allan, 1998;Goldstein, Willner, 2002;Taylor et al, 2011), оскорблений (Muller et al, 2000;Taussig, Litrownik, 1997), девиантности (Krasikova et al, 2013;Lipman-Blumen, 2005), психических расстройств (Morey, 1988;Reich, 1989;Samuel, Widiger, 2008). Деструктивную сторону имеют также лидерство (Ashforth, 1994;Krasikova et al, 2013;Reed, Bullis, 2009) и креативность (Knauss, 1999;Minocha et al, 2014).…”
Section: понятие деструктивностиunclassified